Litter Flammability of 50 Southeastern North American Tree Species: Evidence for Mesophication Gradients Across Multiple Ecosystems - Varner, J. Morgan; Kane, Jeffrey M.; Kreye, Jesse K.; Shearman, Timothy M. (Frontiers in Forests and Global Change, 2021)
Widespread fire exclusion and land-use activities across many southeastern USA forested ecosystems have resulted in altered species composition and structure. These changes in composition and structure have been implicated in positive fire-vegetation feedbacks termed “mesophication” where fire spread and intensity are diminished. In forests and woodlands, inherent flammability of different species is the mechanistic driver of mesophication. To date, there has been limited work on documenting the high diversity of flammability among species in the region, limiting the ability to differentiate among species to restore fuels that sustain fire regimes. Here, we coalesce disparate flammability data and add missing species across the spectrum from species that facilitate fire (so called “pyrophytes”) to those that dampen fire (so called “mesophytes”). We present data on 50 important tree species from across the southeast, all burned using identical laboratory methods. We divide our results for four dominant ecosystems: Coastal Plain uplands, oak-hickory woodlands, Appalachian forests, and bottomland forests. Across ecosystems, the most flammable species were American chestnut (Castanea dentata), a suite of pines (Pinus palustris, P. elliottii, P. serotina, and P. rigida), several oaks (Q. laevis, Q. falcata, Q. margaretta, and Q. alba), and sourwood (Oxydendrum arboreum). At the mesophytic end, the least flammable species were Tsuga canadensis, Acer rubrum, and several other hardwoods previously implicated in mesophication. Each of the four ecosystems we studied contained species that spanned the pyrophytic to mesophytic gradient. These data fill in some key holes in our understanding of southeastern fire adaptations, but also provide context for restoration decisions and fire management prioritization efforts to restore and sustain fire-prone ecosystems of the region.